ANALISIS PERBEDAAN PERTIMBANGAN KEPUTUSAN HUKUM HAKIM DALAM MEMUTUSKAN PERKARA YANG SAMA (PUTUSAN PTUN PONTIANAK) - Arneta, Rada (CONSTITUO : Jurnal Riset Hukum Kenegaraan dan Politik, 2023)
This research entitled Analysis of Differences in Considerations of Judges' Legal Decisions in Deciding the Same Case (Pontianak PTUN Decision) is that land registration is carried out to provide legal certainty for holders of land rights, therefore the Government enforces land registration as stated in the Agrarian Principles. In practice, there are still problems related to land certificates, namely overlapping layers of land title certificates. Pontianak State Administrative Court (PTUN) Decision Number 25/G/2020/PTUN.PTK and Jakarta High Administrative Court (PTTUN) Decision Number 106/B/2021/PT.TUN.JKT are examples of overlapping rights certificate cases on land, raises issues that need to be studied further, namely regarding what is the basis for legal considerations of the judges of PTUN Pontianak and PTTUN Jakarta so that there are differences in decisions in adjudicating cases of overlapping overlapping certificates of land rights in Pontianak PTUN Decision Number 25/G/2020 /PTUN. PTK and Decision of the Jakarta State Administrative High Court Number 106/B/2021 /PT.TUN.JKT. Based on the results of the research conducted, it is known that the differences in legal considerations that occurred in this case were based on the judge's error regarding the calculation of the grace period related to the administrative efforts carried out by PT Bumi Indah Raya as the Plaintiff. The purpose of this study was to see how significant the decision was in In this study, the approach used was descriptive qualitative, meaning that the study was carried out to dig up in-depth information about the object under study. The descriptive method is a procedure for solving problems that are studied in accordance with the facts in the field.